Preoperative Ultrasonography as a Predictor of Difficult Laparoscopic Cholecystectomy that Requires Conversion to Open Procedure - Chand, Prem (Niger J Surg, 2015)
AIM: The present study was conducted to see whether preoperative ultrasonography can be used as a predictor of difficult lapariscopic cholecystectomy or not. METHODS: 50 patients of cholelithiasis, selected from surgical OPD of Rajindra Hospital Patiala, who fulfilled all inclusion and exclusion criteria for the study underwent elective cholecystectomy. Ultrasonography was done pre-operatively on all cases in the same setup and with same probe and patients underwent laparoscopic cholecystectomy in same setup. RESULTS: A significant prediction was found between ultrasonographic parameters and conversion of the procedure to open cholecystectomy which proved that pre-operative ultrasonography is a good predictor of difficulty in laparoscopic cholecystectomy in majority of the cases and should be used as a screening procedure. CONCLUSION: Preoperative ultrasonography should be used as a screening procedure as it is a good predictor of difficulty in laparoscopic cholecystectomy in majority of the cases. It can help surgeon to get an idea of potential difficulty that he can face in the particular patient.